Recovering an undomesticated apostle : essays on the legacy of Paul - Zeichman, Christopher B.; Egger, John A. (Studies in Christianity and Judaism, 2023)
"Paul the apostle is usually imagined as a man of prestige and power--comfortably conversing with philosophers, seeking an audience with the emperor, and composing compelling letters for Christians throughout the Mediterranean. Yet this portrait of a safe and conventional figure at the origins of Christianity airbrushes out many strange things about him. This volume repositions Paul as a man at the periphery of power. Recovering an Undomesticated Apostle explores the ways that Paul has been "domesticated" in both popular and scholarly imagination. By isolating selected crises of the apostle's life and legacy and examining the social and material dimensions of his world, these essays collectively chip away at the received image of his strength and status. The result is a series of glimpses of Paul that frame the apostle as surprisingly marginal and weak within Roman society. Published in honour of New Testament scholar Leif E. Vaage, Recovering an Undomesticated Apostle presents Paul as a man operating from a position of desperation, making virtue out of necessity as he attempted to claw his way up in the dog-eat-dog world of the ancient Mediterranean."--